IMPLEMENTASI DAN PERANCANGAN VOIP SERVER MENGGUNAKAN TRIXBOX OPENSOURCE DAN VPN SEBAGAI PENGAMANAN ANTAR CLIENT - Hasibuan, Muktar; Suharyanto, Cosmas Eko (Computer Science and Industrial Engineering, 2021)
PT. Batam Bintan Telekomunikasi has several employees scattered in several rooms. Communication media is the most important way to maintain communication between employees. Previously, the communication media used in PT Batam Bintan Telecommunication was a PABX (Private Automatic Branch Exchange) phone, but in the PT. Batam Bintan Telekomunikasi has several employees scattered in several rooms. Communication media is the most important way to maintain communication between employees. Previously, the communication media used in PT Batam Bintan Telecommunication was a PABX (Private Automatic Branch Exchange) phone, but in the implementation of PABX the phone is not optimal because each room has only one PABX Line while in one room consists of eight employees. Therefore, it is necessary to optimize communication system between employees of PT Batam Bintan telecommunications. Communication system optimization is done by implementing Voice over Internet Protocol (VoIP) as pabx replacement communication media. Voip is implemented using Trixbox server, SIP phone, Zoiper, MicroSIP as an application to make calls on client computers and VPN as security between clients. Each employee will be created a VoIP account that is listed on the trixboxx server by providing a telephone number and password on the VoIP account.Based on the results of the study, the application of VoIP on computers in the PT environment. Batam Bintan telecommunications connected by Trixbox server, VoIP can facilitate communication between employees that is useful to support employee performance. With this VoIP is expected to replace the previous communication used in PT. Batam Bintan Telekomunikasi is by replacing PABX with VoIP by utilizing internet facilities at PT. Batam Bintan Telecommunications.